AB0665 Apparent Late TNFI Secondary Treatment Failure in Axial Spondyloarthritis. (10th June 2014) - Thorne, I.; Hayward, R.; Harris, C.; Sengupta, R.; Smith, A.; Gaffney, K.; Leeder, J.; Rowell, S.; Keat, A.
Abstract : Background: Secondary failure of TNF inhibitor (TNFi) treatment in ankylosing spondylitis (AS) and axial spondyloarthritis (axSpA) is an important clinical problem. Clear guidelines for discontinuing biologic treatment exist, based on persistence or recurrence of symptoms, reflected by the Bath Ankylosing Spondylitis Activity Index (BASDAI) and visual analogue scale spinal pain (VAS-SP) scores. Treatment reviews in our units indicated that some patients who initially responded well to TNFi continued on treatment in spite of measurements of BASDAI and/VAS SP at levels indicative of secondary treatment failure. Since the BASDAI is a subjective measure patients' perceptions of symptom severity may vary over time irrespective of treatment efficacy. Objectives: To identify patients on long-term TNFi who met National criteria for cessation or change of treatment after initial response, an audit of SpA databases at three centres was conducted retrospectively to identify real and apparent treatment failures. Methods: All patients who had received TNFi for over 250 weeks were auditted, including ptients who had switched TNFi. Sequential BASDAI and VAS-SP scores were recorded, as were erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) where available and evidence of co-morbidities. We defined "treatment failure" as a return of BASDAI and/or VAS SP levels to within 2 units of the pre-treatment levels (NICE criteria) and "BASDAI rise" as 3 successive increases in scores. The lowest BASDAI recorded over the observation period (nadir) was also identified. Results: Anonymised data were collected for 129 axial SpA patients, with median treatment duration 374 weeks. Pre-treatment and nadir data (median) are summarised in Table 1 . TNFi treatment failure was seen in 80 (62%). Amongst these three patterns were seen: 1) Transient episode of "apparent failure" (a single "failure score") followed by return to a sustained TNFi response (in 30); 2) Failure on 2 or more consecutive occasions but subsequent return to otherwise a sustained TNFi response (in 20); 3) Persistent failure was observed in 30 (and this resulted in 14 switching TNFi). During the period of observation, BASDAI rise occurred in 58 (45%). Comparing the BASDAI rise group to those without revealed no difference between BASDAI, VAS-SP, CRP or ESR at baseline or at nadir. BASDAI rise was not predictive of TNFi treatment failure. Conclusions: We have observed more apparent than true secondary failures of TNFi when used long-term in the treatment of axSpA. This may reflect flares, comorbidities or the tendency of symptomatic clinical measures to revert to the mean. True treatment failure was only observed in 23%. In a condition with few treatment options care must be taken to avoid unnecessary treatment changes on the basis of apparent but not true secondary treatment failure. Other scoring systems, including measures of function, metrology, quality of life and inflammation are therefore important elements of assessments of disease activity. References: National Institute for Health and Care Excellence (2008) Adalimumab, etanercept and infliximab for ankylosing spondylitis. TA143. London: National Institute for Health and Care Excellence. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4137